Persepsi Mahasiswa Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Sumatera Utara terhadap Pancasila sebagai Ideologi Negara - Ritonga, Alwi Dahlan; Kusmanto, Heri (Politeia: Jurnal Ilmu Politik, 2018)
This study is the study of the perception of the Students against the State ideology Pancasila at the USU EXTENSION. Focus students ' perceptions of SOCIAL about how discuss USU against Pancasila. The findings of this study, among others, there are three things that become indicators of students ' perception in seeing against Pancasila. First, the indicators of cognition to see the level of knowledge of students against Pancasila; Second, indicators of students ' feelings of affection to see concerns the emotional aspects toward Pancasila; Third, the evaluative indicators to see objectively based on student assessment of cognition and affection they have associated the Pancasila. The method used is the method diskriptif-quantitative data collection techniques with the shape of the survey (questionnaire) and data analysis techniques using univarial analysis with a single table.